Global reformations
1 online resource
Keywords: "Global Reformations offers a sustained, comparative, and interdisciplinary exploration of religious transformations in the early modern world. Exploring the convergence of religious reform, global expansion, and governmental consolidation, it asks how a global frame complicates our understanding of what the Reformation itself was and offers a unique and up-to-date examination of the Reformation. Demonstrating new research and innovative approaches in the study of cross-cultural contact during the early modern period, this volume is ideal for advanced undergraduates and graduates of Early Modern History, Religious History, Women & Gender Studies and Global History"--